Developing skills in grammar & composition 1 - Ramos, Carmen M.; Sanchez, Amelia C. (Pioneer St., Mandaluyong City, 1986)
This book was designed as a textbook as well as a workbook. It was prepared with the aim of helping Filipino students meet their needs in their study of English. The authors are aware of the difficulties met by Filipinos in learning English
Keywords: English language- Grammar